2005
DOI: 10.1111/j.1445-2197.2005.03478.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term survival outcomes following breast cancer surgery in Western Australia

Abstract: Despite overall improvements in survival of women diagnosed with breast cancer in Western Australia, initial surgical treatment in public hospitals outside of Perth was associated with significantly poorer outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 28 publications
3
37
0
Order By: Relevance
“…We found no difference in the proportion of patients from metropolitan and rural areas offered curative procedures at the tertiary centre participating in our study. This is similar to another WA study that demonstrated little difference in the surgical treatment of colorectal cancer between rural and metropolitan areas [20], but in contrast with breast cancer and prostate cancer surgical treatment patterns that were reported to vary significantly by residential location [21,22]. It is reassuring that cancer patients with limited curative options living in rural areas are not being disadvantaged in terms of treatment decisions.…”
Section: Impact Of Geography and Demographysupporting
confidence: 83%
See 1 more Smart Citation
“…We found no difference in the proportion of patients from metropolitan and rural areas offered curative procedures at the tertiary centre participating in our study. This is similar to another WA study that demonstrated little difference in the surgical treatment of colorectal cancer between rural and metropolitan areas [20], but in contrast with breast cancer and prostate cancer surgical treatment patterns that were reported to vary significantly by residential location [21,22]. It is reassuring that cancer patients with limited curative options living in rural areas are not being disadvantaged in terms of treatment decisions.…”
Section: Impact Of Geography and Demographysupporting
confidence: 83%
“…Previously 20% of patients with lung cancer were reported to have surgery in Western Australia similar to the 21% reported here [23]. Radiotherapy rates appear to be increasing in more recent times with 52% reported in this 2006-07 study compared to 39% of lung cancer patients having radiotherapy in New South Wales in 2002 [22]. Similarly chemotherapy rates have increased from 39% in 2002 to the 49% found in this study.…”
Section: Treatment and Survivalsupporting
confidence: 76%
“…Other evidence of differential survival between ethnic groups has primarily arisen from the United States, where African American women have poorer survival than White women (O'Malley et al 2003, Curtis et al 2008, Du et al 2008. In other countries, ethnic differences have also been found, with lower survival in Indigenous compared to White Australians (Spilsbury et al 2005) and better survival in South Asian and Chinese compared to other women in the UK (Dos Santos Silva et al 2003, Velikova et al 2004, Jack et al 2009.…”
Section: Introductionmentioning
confidence: 93%
“…Survival was higher in private hospitals compared to public hospitals. The survival disadvantage in rural hospitals was confirmed in another study based on the Western Australia Data Linkage System using 11,445 women treated between 1982 and 2000 [30]. A significantly increased mortality risk was observed for women who underwent initial surgical treatment in regional public hospitals outside of the state capital, Perth.…”
Section: Influence Of Hospital Setting On Outcomementioning
confidence: 61%